2010
DOI: 10.1143/jpsj.79.024001
|View full text |Cite
|
Sign up to set email alerts
|

Space Efficient Opposed-Anvil High-Pressure Cell and Its Application to Optical and NMR Measurements up to 9 GPa

Abstract: We have developed a new type of opposed-anvil high pressure cell with substantially improved space efficiency. The clamp cell and the gasket are made of non-magnetic Ni-Cr-Al alloy. Non-magnetic tungsten carbide (NMWC) is used for the anvils. The assembled cell with the dimension 29 mm  41 mm is capable of generating pressure up to 9 GPa over a relatively large volume of 7 mm 3 . Our cell is particularly suitable for those experiments which require large sample space to achieve good signal-to-noise ratio, suc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 31 publications
(60 reference statements)
0
32
0
1
Order By: Relevance
“…However, the pressure and temperature ranges in the previous studies were far from the magnetic QCP. By utilizing the recently developed highpressure techniques [19][20][21][22][23], we have reinvestigated this problem in an extended pressure and temperature range, and surprisingly found that MnP becomes superconducting below T sc ≈ 1 K near the magnetic QCP at P c ≈ 8 GPa.…”
mentioning
confidence: 99%
“…However, the pressure and temperature ranges in the previous studies were far from the magnetic QCP. By utilizing the recently developed highpressure techniques [19][20][21][22][23], we have reinvestigated this problem in an extended pressure and temperature range, and surprisingly found that MnP becomes superconducting below T sc ≈ 1 K near the magnetic QCP at P c ≈ 8 GPa.…”
mentioning
confidence: 99%
“…Masashi TAKIGAWA 1 We describe our recent progress in high-pressure nuclear magnetic resonance (NMR) technique, which extends the range of practical NMR experiments to 10 GPa-class. The new opposed-anvil type cell has significantly large sample space, though the whole clamp cell size is small enough to put within superconducting magnets or fridges.…”
Section: 瀧川 仁 mentioning
confidence: 99%
“…The pressure cell, a CuBe based piston-cylinder design had been used by a collaborating group at Cambridge University for De Haas-van Alphen type of studies [25], and was retrofitted for NMR in Leipzig. Simultaneously, in 2009, Kitagawa introduced [26] a clamp cell design made of a Ni-Cr-Al alloy and non-magnetic tungsten carbide anvils, allowing for relatively large sample volumes of several cubic millimeters; focusing their investigations on heavy fermionic systems [27][28][29] at pressures up to 10 GPa [30].…”
Section: Introductionmentioning
confidence: 99%